Prevalence and risk factors for hypertension among children and adolescents in Shaanxi province, Northwestern China, according to the three hypertension guidelines - Minmin Li; Nan Yang; Jingjun Zhao; Xinyan Wang; Qianyun Wang; Tong Hui; Wei Shi; Ruhai Bai (Scientific Reports)
Abstract This study aimed to examine the prevalence and epidemiological characteristics of hypertension among children and adolescents aged 7–17 years in Shaanxi Province using three hypertension guidelines for children and adolescents. Data from the 2023 Shaanxi Student’s Health Surveillance Survey were used. Hypertension was defined according to three references, namely, the 2018 National Health Commission of the China (NHCC) pediatric blood pressure reference, the 2017 American Academy of Pediatrics (AAP) clinical practice guidelines, and the 2016 European Society of Hypertension guidelines (ESH). A log-binomial regression model was applied to assess the associations between hypertension and possible risk factors. A total of 220,497 students with an average age of 11.73 years were included in the analysis. The prevalence of hypertension was 11.73%, 15.75% and 10.04% according to the NHCC, AAP and ESH guidelines, respectively. All three guidelines suggest that children who were overweight or obese or who lived in rural areas had significantly greater odds of having hypertension, and central and southern Shaanxi students had significantly lower odds of having hypertension. All three guidelines show that hypertension in children and adolescents seems to be a serious health problem in Shaanxi Province as well as in Northwestern China; thus, policymakers and public health practitioners should take immediate action to address the already established modifiable risk factors.